PERFIL DA PRODUÇÃO ACADÊMICA SOBRE A REDE GLOBO DE TELEVISÃO - Lucio, Taís Vargas Freire Martins (2008)
This work has as an objective to trace the profile of the academic production on the Globo Network Television. For this, we use as source research works of master s degree dissertations and doctorate thesis defended in pos-graduate programs in Brazil in repertoried bank of thesis of CAPES. 145 academic publications in the period of 1987 through 2006 had been analyzed. In the analytical approach of the profile of this production we distinguish: year of production; institution of origin; geographic region; academic level, area of study and gender of the authors.(AU)